"Just got to live life as it comes": A case study of the spousal-dyad longitudinal mild stroke transitional experience. (29th July 2019) - Hodson, Tenelle; Gustafsson, Louise; Cornwell, Petrea
ABSTRACT: Objective : To longitudinally explore the transition home for a spousal dyad following mild stroke, in the context of a mild stroke-specific health service. Research Design : A case study approach, using an Interpretative Phenomenological Analysis (IPA), was identified as suitable for this study, as it enabled the essence of the phenomenon to be examined. Method : Participants were purposively chosen from a Randomised Control Trial (RCT), to reflect the average age, gender and marital status of the mild stroke population. The participants were a male (age 64) and his wife (age 62). Participants received the RCT intervention. Semi-structured interviews were completed separately with participants at 1-, 3-, 6- and 9- months post stroke. Results : Two themes were identified: (1) The Unexpected, Undesirable and Short-Lived, and (2) The New 'Normal'. The first theme reflects the confusion, adjustment and adaptation that occurred for the couple, especially during the first month at home. The second represents the couple's journey back to their everyday lives following hospital discharge, but also the questions and changes that remained present at 9-months post-discharge. Conclusions : Themes demonstrate an ongoing process of adjustment and the contextual nature of the transitional experience. Results also indicate the need to ensure that individuals have access to mild-stroke specific information across the transition continuum.